Enzymatic removal of inhibitory compounds from lignocellulosic hydrolysates for biomass to bioproducts applications - Tramontina, Robson; Brenelli, Lívia Beatriz; Sodré, Victoria; Franco Cairo, João Paulo; Travália, Beatriz Medeiros; Egawa, Viviane Yoshimi [UNESP]; Goldbeck, Rosana; Squina, Fabio Marcio (Springer Nature, 2020)
The physicochemical pretreatment is an important step to reduce biomass recalcitrance and facilitate further processing of plant lignocellulose into bioproducts. This process results in soluble and insoluble biomass fractions, and both may contain by-products that inhibit enzymatic biocatalysts and microbial fermentation. These fermentation inhibitory compounds (ICs) are produced during the degradation of lignin and sugars, resulting in phenolic and furanic compounds, and carboxylic acids. Therefore, detoxification steps may be required to improve lignocellulose conversion by microoganisms. Several physical and chemical methods, such as neutralization, use of activated charcoal and organic solvents, have been developed and recommended for removal of ICs. However, biological processes, especially enzyme-based, have been shown to efficiently remove ICs with the advantage of minimizing environmental issues since they are biogenic catalysts and used in low quantities. This review focuses on describing several enzymatic approaches to promote detoxification of lignocellulosic hydrolysates and improve the performance of microbial fermentation for the generation of bioproducts. Novel strategies using classical carbohydrate active enzymes (CAZymes), such as laccases (AA1) and peroxidases (AA2), as well as more advanced strategies using prooxidant, antioxidant and detoxification enzymes (dubbed as PADs), i.e. superoxide dismutases, are discussed as perspectives in the field.
Keywords: Biorefinery; Detoxification enzymes; Fermentation; Inhibitory compounds; Lignin; Lignocellulose